Análisis de las condiciones bajo las cuales se produce un abuso de posición de dominio por ventas atadas y sus posibles justificaciones (Tema Central) - Cárdenas Garzón, Viviana Carolina (2016)
This paper is structured in four sections. The first try to determine the meaning of tying, and when a practice can be under that definition; the second talk about the types of bonding, where tying and bundling are defined to be able to distinguish each other; the third it is determined the different behavior influences in the market of the principal product and the secondary product; finally, the fourth explain possible justifications for conduct, paying attention specially about legal justification, technical justification, safety or public health reasons and economic reasons, known as market efficiencies. This article seeks to establish certain parameters that allow understanding the authorities of control of market power, users, consumers and economic operators when a behavior requires a sanction.